Increasing the Variety of Vegetable Products Using Hydroponic Formulation Technology - Nur Kholida Wulansari; Dewanti Risa Utami; Endang Warih Minarni (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Demand for horticultural commodities, especially vegetables, continues to increase along with population and prosperity. As science and technology develop, society becomes aware of the importance of providing healthy, pesticide-free food, and hydroponic vegetable cultivation is starting to attract the public. The method used in service activities is technology transfer/socialization regarding the need for product variations. The transfer of material will illustrate that the more types of products provided, the more attractive consumers will be. After the outreach activities, there was an increase in understanding of the hydroponic cultivation of cherry tomatoes. The product that will be developed in this activity is cherry tomatoes. Cultivating cherry tomatoes, making installations, and making nutritional formulas. Furthermore, after socialization, assistance was provided in the cultivation process, making installations, and making nutritional formulas. This community service activity does not only involve staff CV. Pesona21 also involves street vendors and apprentice students. Expansion of cherry tomato products begins with the installation and preparation of planting media. Next, care is carried out until the hydroponic cherry tomatoes are harvested.